The teaching task. A necessary tool in medical training - Alexis Díaz Brito; Dunia Maria Chavez Amaro (Medisur)
The teaching task is the core of the independent activity and is centered on the joint interaction between the teacher and the student. In higher education this constitutes a favorable way to establish the different subjects interrelation of the contents, with the problems of the profession. It is necessary to emphasize that, during the undergraduate training in the Medical Sciences career; the teaching tasks must reveal the fusion of instruction and education as a fundamental premise in the relationship of the teacher-student binomial. In this training process, both parties enrich their knowledge and develop skills for solving more complex concrete problems. In this article, the authors reflect on the conception of the teaching task as a primary link in the teaching-learning process, given the close connection between the pedagogical organization of students' self-preparation and the development of cognitive independence in them.